Youth screen use in the ABCD® study - Bagot, K S; Tomko, R L; Marshall, A T; Hermann, J; Cummins, K; Ksinan, A; Kakalis, M; Breslin, F; Lisdahl, K M; Mason, M; Redhead, J N; Squeglia, L M; et al. (Developmental cognitive neuroscience, 2022)
Adolescent screen usage is ubiquitous and influences development and behavior. Longitudinal screen usage data coupled with psychometrically valid constructs of problematic behaviors can provide insights into these relationships. We describe methods by which the screen usage questionnaire was developed in the Adolescent Brain Cognitive Development (ABCD) Study, demonstrate longitudinal changes in screen usage via child report and describe data harmonization baseline-year 2. We further include psychometric analyses of adapted social media and video game addiction scales completed by youth. Nearly 12,000 children ages 9-10 years at baseline and their parents were included in the analyses. The social media addiction questionnaire (SMAQ) showed similar factor structure and item loadings across sex and race/ethnicities, but that item intercepts varied across both sex and race/ethnicity. The videogame addiction questionnaire (VGAQ) demonstrated the same configural, metric and scalar invariance across racial and ethnic groups, however differed across sex. Video gaming and online social activity increased over ages 9/10-11/12 (p's < 0.001). Compared with boys, girls engaged in greater social media use (p < .001) and demonstrated higher ratings on the SMAQ (p < .001). Compared with girls, boys played more video games (p < .001) and demonstrated higher ratings on the VGAQ (p < .001). Time spent playing video games increased more steeply for boys than girls from age 9/10-11/12 years (p < .001). Black youth demonstrated significantly higher SMAQ and VGAQ scores compared to all other racial/ethnic groups. These data show the importance of considering different screen modalities beyond total screen use and point towards clear demographic differences in use patterns. With these comprehensive data, ABCD is poised to address critical questions about screen usage changes across adolescence.
Keywords: průzkumy a dotazníky; Female; dítě; ženské pohlaví; Surveys and Questionnaires; Children; Adolescent Behavior; Adolescent; lidé; Self-report; Screen usage; Male; mladiství; videohry; ABCD; Video Games; Child; Social Behavior; mužské pohlaví; sociální chování; chování mladistvých; Humans